Liposomes – metabolically active drug transport systems: visualization and pharmacokinetic. Part 2 (review) - O. N. Pozharitskaya; Yu. M. Kozur; S. S. Osochuk; E. V. Flisyuk; I. E. Smekhova; S. D. Malkov; K. O. Zarifi; I. A. Titovich; E. K. Krasova; A. N. Shikov (Разработка и регистрация лекарственных средств, 2024)
Introduction. In the second part of the review we discussed aspects of visualization, pharmacokinetics and biodistribution of liposomes.Text. Many different methodsh as been proposed for the visualization of liposoms morphology and quality such as light microscopy, ESEM, TEM, AFM, etc. Each method have own advantages and limitations which are discussed in the article: In general, the selection of method depends on the specific morphological characteristics and level of details. It is important to understand the specificity of the liposomes and the visualization method for correct preparation of samples. Adequately performed pharmacokinetic and biodistribution studies can also be used as a tool for liposome visualization. The nature of active pharmaceutical ingredients, dose, lipid components, size of liposomes, charge, coating of liposomes with excipients and route of administration significantly affects the pharmacokinetics of liposomal forms. Additionally, the interaction of liposomal forms with the immune system, reticuloendothelial system and blood components play an important role in their absorption, distribution and elimination.Conclusion. The better understanding of the absorption, biodistribution, metabolism and clearance of liposomal formulations is essential for the development of modern drugs.